2020
DOI: 10.1038/s41598-020-59731-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale exploration of transcriptional regulation in the nisin Z producer Lactococcus lactis subsp. lactis IO-1

Abstract: Transcription is of the most crucial steps of gene expression in bacteria, whose regulation guarantees the bacteria's ability to adapt to varying environmental conditions. Discovering the molecular basis and genomic principles of the transcriptional regulation is thus one of the most important tasks in cellular and molecular biology. Here, a comprehensive phylogenetic footprinting framework was implemented to predict maximal regulons of Lactococcus lactis subsp. lactis IO-1, a lactic acid bacterium known for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 88 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…The query sequence showed a conserved domain similar to nisin_A. Nisin Z differs from the typical nisin A peptide by only one amino acid, resulting in greater solubility at physiological pH, making it a more suitable candidate for biomedical applications [ 39 ]. Likewise, the nisin_Z class was found in L. lactis KF282 but not in L. lactis ATCC19435 or L. lactis ATCC11474 ( Figure 5 B).…”
Section: Resultsmentioning
confidence: 99%
“…The query sequence showed a conserved domain similar to nisin_A. Nisin Z differs from the typical nisin A peptide by only one amino acid, resulting in greater solubility at physiological pH, making it a more suitable candidate for biomedical applications [ 39 ]. Likewise, the nisin_Z class was found in L. lactis KF282 but not in L. lactis ATCC19435 or L. lactis ATCC11474 ( Figure 5 B).…”
Section: Resultsmentioning
confidence: 99%
“…Glucose serves as a primary carbon source for microorganisms, and prior empirical findings have demonstrated that the expression of seven crucial mRNAs related to carbohydrate transport is notably elevated under conditions of low glucose levels. Notably, the genes mtlA (gene0435) and celB (gene3876, gene3860) are prevalent across various strains, including Vibrio cholerae, Escherichia coli, Lactococcus lactis, Clavibacter michiganensis, and Listeria monocytogenes [105][106][107][108]. The subsequent research direction of our team involves utilizing mtlA (gene0435) and celB (gene3876 and gene3860) as bio-alert indicators to assess the nutrient status of soil based on their expression.…”
Section: Discussionmentioning
confidence: 99%
“…Under stress conditions LAB use the malolactic fermentation pathway where the CO 2 produced is transformed into bicarbonate by carbonic anhydrases to increase the intracellular pH [39]. Finally, ars operons are widely distributed in bacterial genomes, including LAB, such as Lactococcus lactic [48]. The protein ArsC is an enzyme reducing arsenate to arsenite, protecting the cell from high concentrations of arsenic [49].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%